2001
DOI: 10.1530/eje.0.1450799
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced insulin resistance and pancreatic adaptive response in aging rats are not modified by oral vanadyl sulfate treatment

Abstract: Objective: To explore the adaptive response of the endocrine pancreas in vivo and in vitro and the possible beneficial effect of the insulino-mimetic agent vanadyl sulfate (VOSO 4 ), using glucocorticoid treatment to increase insulin resistance, in aging rats. Design and Methods: Dexamethasone (Dex) (0.13 mg/kg b.w.) was administered daily for 13 days to 3-and 18-month old Sprague-Dawley rats and oral VOSO 4 was given from the 5th day. Plasma glucose, insulin and free fatty acids (FFA) concentrations were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 39 publications
9
39
0
Order By: Relevance
“…Several studies show that glucocorticoids induce peripheral insulin resistance, in vivo and in vitro 5,8,[23][24][25][26] , by increasing hepatic glucose output and decreasing the peripheral glucose uptake. There are evidences that ROS' production plays a fundamental role on developing insulin resistance by being responsible for the smaller capture of glucose on muscle 27 and on adipose tissue 28 .…”
Section: All Procedures With Animals Have Been Approved Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that glucocorticoids induce peripheral insulin resistance, in vivo and in vitro 5,8,[23][24][25][26] , by increasing hepatic glucose output and decreasing the peripheral glucose uptake. There are evidences that ROS' production plays a fundamental role on developing insulin resistance by being responsible for the smaller capture of glucose on muscle 27 and on adipose tissue 28 .…”
Section: All Procedures With Animals Have Been Approved Bymentioning
confidence: 99%
“…The reduction of weight in rats 2,3 . The increase on serum glucose and serum insulin [4][5][6] . Loss in muscle mass associated to liver hypertrophy 7 .…”
Section: Introductionmentioning
confidence: 99%
“…All remaining animals received a single 50 mg/kg dose of MPL sodium succinate (Pharmacia-Upjohn Company, Kalamazoo, MI, USA) via the cannula over 30 s. Rats (3) were sacrificed by exsanguinations under anesthesia at 0.25, 0.5, 0.75, 1, 2, 4, 5, 5. 5,6,7,8,12,18,30,48 and 72 h after dosing. The sampling time points were selected based on previous studies describing glucocorticoid response dynamics and enzyme induction in skeletal muscle and liver.…”
Section: Experimental Designmentioning
confidence: 99%
“…A primary substrate for gluconeogenesis is amino acid carbon derived from the net degradation of muscle protein. Glucocorticoids also cause muscle to become insulin resistant, thereby preventing the large bulk of the musculature from taking up the glucose produced by the liver and kidney [4,5,12]. When corticosteroids are used therapeutically, their effects on the musculature are accentuated, which results in muscle wasting and insulin-resistant diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…This GC-induced IR is time-, dose-and agedependent (Novelli et al, 1999;Rafacho et al, 2011) and is a common effect in GC-treated rats. This is supported by the fact that most studies showed fasting hyperinsulinemia, an indicator of IR (Lee et al, 1989;Stojanovska et al, 1990;Koranyi et al, 1992;Novelli et al, 1999;Zakrzewska et al, 1999;Barbera et al, 2001;Holness & Sugden, 2001;Karlsson et al, 2001;Severino et al, 2002;Choi et al, 2006;Giozzet et al, 2008;. This rise in circulating insulin concentrations fully compensates for peripheral IR in normal rats and prevents any increase in blood glucose concentrations (Lee et al, 1989;Koranyi et al, 1992;Ogawa et al, 1992;Novelli et al, 1999;Zakrzewska et al, 1999;Barbera et al, 2001;Holness & Sugden, 2001;Severino et al, 2002;Choi et al, 2006;Giozzet et al, 2008;, except in normal elderly rats (Novelli et al, 1999) or when the highest experimental doses (1 mg/kg.…”
Section: Glucose Tolerance and Insulin Sensitivity In Gc-treated Ratsmentioning
confidence: 89%